Deteksi Dini Perilaku Depresi pada Siswa Sekolah Menengah - Sindi Putri Ayu; Finkah Sabillah; Nurhidayah Nurhidayah; Bilqis Salsabila; Risma Anita Puriani; Rizki Novirson (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Depression in adolescents, especially high school students, is a serious mental health problem with significant impacts on psychological well-being, academic performance, and social life. Risk factors such as academic pressure, family conflict, negative mindset, and social media addiction contribute to the increasing prevalence of depression. Early detection in the school environment is a critical step to prevent adverse effects such as self-harm and suicidal ideation. Depression in adolescents is multifactorial and requires a holistic approach. Early detection through symptom screening, mental health education, and school-family-professional collaboration are essential preventive strategies. Recommendations include the integration of mental health modules into the school curriculum and teacher training for early risk identification.